Theabrownin-targeted regulation of intestinal microorganisms to improve glucose and lipid metabolism in Goto-Kakizaki rats. Issue 4 (28th January 2022) - Yue, Suijuan; Shan, Bo; Peng, Chunxiu; Tan, Chao; Wang, Qiuping; Gong, Jiashun
Abstract : TB-targeted regulation of intestinal microorganisms Bacteroides thetaiotaomicron (BT), Lactobacillus murinus (LM), Parabacteroides distasonis (PD) and Bacteroides acidiciens (BA) to improve glucolipid metabolism in Goto-Kakizaki rats. Abstract : Diabetes is a disease that is characterized by a disturbance of glucose metabolism. Theabrownin (TB) is one of the most active and abundant pigments in Pu-erh tea, and it is a brown pigment with multiple aromatic rings and attached residues of polysaccharides and proteins. TB has been shown to be hypolipidemic and displays fasting blood glucose (FBG)-lowering properties in rats fed a high-fat diet, but the underlying mechanism has not been elucidated. This study aimed to determine the effect of TB in treating diabetes and explore the underlying mechanism of action of intestinal microbes by using Goto-Kakizaki (GK) rats. Diabetic GK rats were treated up to 8 weeks with TB (GK-TB). Following treatment, the body weight, triglyceride (TG) content, fasting blood glucose (FBG) content, and Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) were significantly lower in the GK-TB group than in the GK control group ( P < 0.05). Meanwhile, the circulating adiponectin (ADPN), leptin, and glucokinase levels in the serum of the GK-TB group were significantly higher than those in the GK group, while there was little difference in hepatic lipase (HL) and hormone-sensitive triglyceride lipase (HSL) enzyme activities ( P > 0.05). Furthermore, with the extension of treatment time, the number of unique intestinal microorganisms in GK rats greatly increased and an interaction among intestinal microorganisms was observed. The Firmicutes / Bacteroides ratio was decreased significantly, and the composition of Actinobacteria and Proteobacteria was increased. The use of multiple omics technologies showed that TB is involved in the targeted regulation of the core characteristic intestinal flora including Bacteroides thetaiotaomicron (BT), Lactobacillus murinus (LM), Parabacteroides distasonis (PD), and Bacteroides_acidifaciens (BA) which improved the glucose and lipid metabolism of GK rats via the AMP-activated protein kinase signaling pathway, insulin signaling pathway, bile secretion and glycerophospholipid metabolism. Intragastric administration of BT, LM, PD, or BA led to a significantly reduced HOMA-IR in GK rats. Furthermore, BT significantly reduced serum lipid TG and total cholesterol (TC) and BA significantly reduced the serum lipid TC and low-density lipoprotein (LDL). PD significantly reduced serum LDL, while the effect of LM was not significant. However, LM and PD significantly increased the content of ADPN in serum. Taken together, our results indicated that the effect of TB on diabetic rats mainly depends on the targeted regulation of intestinal microorganisms and that TB is a functional food component with great potential to treat or prevent diabetes.